Effects of running in minimal, maximal and traditional running shoes: a musculoskeletal simulation exploration using statistical parametric mapping and Bayesian analyses. (4th May 2021) - Sinclair, Jonathan; Brooks, Darrell; Taylor, Paul John; Liles, Naomi Bernadette
Abstract: The current study aimed to use a musculoskeletal simulation approach to examine running biomechanics in minimal, maximal and traditional running shoes using a concurrent SPM and Bayesian approach. Thirteen male participants ran over a force platform at 4.0 m/s in minimal maximal and traditional running shoes. Lower extremity joint loading and muscle forces were explored using a musculoskeletal simulation approach. Differences between conditions were examined using statistical parametric mapping (SPM) and Bayesian one-way repeated measures ANOVA. Bayesian analyses showed that traditional running shoes increased vastus intermedius (208.8BW·ms), vastus lateralis (320.2BW·ms) vastus medialis (188.7BW·ms), lateral tibiofemoral (495.9BW·ms) and patellofemoral joint stress (1683.4KPa/BW·s) integrals compared to minimal running shoes (185.0BW·ms, 281.9BW·ms, 167.2BW·ms, 456.5BW·ms & 1524.9KPa/BW·s). Furthermore, SPM showed that minimal footwear increased glutaeal, medial tibiofemoral and hip forces during the first 10% of the stance phase and Achilles tendon forces from 20 to 40% stance compared to traditional running shoes, whereas Bayesian analysis showed that minimal footwear increased loading rates (366.9BW/s) compared to maximal and traditional running shoes. (186.5BW/s) and traditional running shoes (161.5BW/s). Finally, SPM also showed that maximal footwear enhanced ankle eversion from 10 to 30% of stance compared to both minimal and traditional running shoes. This study therefore shows that minimal footwear may place runners at increased risk from impact related chronic injuries yet attenuate risk from patellofemoral and lateral tibiofemoral pathologies compared to traditional running shoes. In addition, owing to increases in ankle eversion, maximal running shoes may enhance risk to the aetiology of medial tibial stress syndrome compared to minimal and traditional running shoes.